Effect of 17α Methyltestosterone on sex reversal of Xiphophorous maculatus platy and Cyprinus carpio Koicarp - Y, Ananth kumar; Haniffa, Mohamed Abdul Kadher (Journal of Research in Biology, 2011)
Hormone sex manipulation role of the masculinizing hormone 17aMTS was tested in platy Xiphophorous maculatus and koicarp Cyprinus carpio. The fry of platy and koicarp of the first group were fed 17 α- MTS hormone incorporated diet for 90 days. And the other groups were immersed with the hormone for 6h. The hormone incorporated feed at 500mg/l produced 68% males in koicarp and 80% in platy. According to immersion technique 400mg/l produced 85% in platy and 75% in koicarp. Exposure to other concentrations of 17 α- MTS at varying durations invariably produced intersex individuals. From the present study it is concluded that Koicarp and Platy are amenable to endocrine sex reversal by steroid immersion and dietary treatments of fry